ANALISIS HUKUM TENTANG PEMILIKAN SAHAM PADA PERUSAHAAN PENANAMAN MODAL ASING - SRI YULIATI (PREMISE LAW JURNAL, 2013)
ABSTRACT Foreign investment is highly needed by Indonesia since it gives positive impact on the nation building; therefore, the Indonesian government attempts to invite foreign investors because they bring their dollars which can finance a number of projects in Indonesia. The projects will give big influence on various aspects of life such as manpower, local economic condition, the increasing regional revenue, the increasing national reserves, etc. The problems of the study were as follows: first, how about the regulation of the ownership of foreign stocks by foreign capital investors in Indonesia; secondly, what would occur when foreign investors sold their stocks to domestic investors; and thirdly, how about the regulation on divestment of foreign investors’ stocks in Indonesia. In order to study these problems, the researcher conducted descriptive analytic study and library research with judicial normative method. Keywords: Stock Ownership, Foreign Capital Investment